Body composition in urban South Asian women; development of a bioelectrical impedance analysis prediction equation - Waidyatilaka, Indu; Lanerolle, Pulani; de Lanerolle-Dias, Maduka; Atukorala, Sunethra; de Silva, Angela (Annals of human biology, 2013)
Abstract Background: Assessment of body composition plays a significant role in combating chronic disease among South Asians. Accurate assessment of body composition by bioelectrical impedance analysis (BIA) requires population-specific equations which are currently unavailable for urban South Asian women. Aim: To assess validity of direct BIA assessment and selected equations for prediction of total body water (TBW), against Deuterium (2H2O) dilution and develop and validate a population-specific TBW equation for urban South Asian women. Subjects and method: Data of 80 urban Sri Lankan women (30-45 years) were used for this analysis. Body composition was assessed by 2H2O dilution (reference) and BIA. Available BIA equations were assessed for validity. A new TBW equation was generated and validated. Results: Direct BIA measurements and other equations did not meet validation criteria in predicting TBW. TBW by the new equation (TBW = 3.443 + 0.342 × (height2/impedance) + 0.176 × weight) correlated (p < 0.001) with TBW by reference method. TBW using the new equation was not significantly different (25.30 ± 2.4 kg) from the reference (25.32 ± 2.7 kg). Conclusion: Direct use of TBW by instrument and existing equations are less suitable for this population. The new TBW equation is suitable for body composition assessment in urban South Asian women.